Spatial Reasoning and Its Contribution to Mathematical Performance Across Different Content Domains: Evidence from Chinese Students - Tianshu Xu; Siyu Sun; Qiping Kong (Journal of Intelligence)
Recent studies have provided convincing evidence highlighting the strong relationship between spatial reasoning and mathematical performance. However, there is a limited body of research exploring the contributions of different spatial reasoning constructs to mathematical performance across various content domains, particularly within non-Western contexts. This study investigates the relationship between spatial reasoning skills—including mental rotation, spatial visualization, and spatial orientation—and mathematical performance across various domains (number, geometric shapes and measures and data display) among Chinese elementary school students in grade four (ages 9–10). The results indicate that overall spatial reasoning significantly predicts mathematical performance across various domains. All three spatial reasoning constructs significantly contribute to performance in the number and geometric shapes and measures domains, with mental rotation and spatial orientation being the strongest predictors of performance in these respective content domains. For data display performance, spatial orientation and spatial visualization significantly contribute, with spatial visualization being the strongest predictor. Although no significant gender differences were found in the overall link between spatial reasoning and mathematical performance, subgroup regression analysis showed variations. For male students, spatial orientation was the main predictor across content areas. For female students, mental rotation was the key predictor for number and geometry, while spatial visualization was most significant for data display.